2022
DOI: 10.3390/diagnostics12123125
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Reproducibility of Radiomic Features Based on Various Segmentation Techniques on Cervical Cancer DWI-MRI

Abstract: Cervical cancer is the most common cancer and ranked as 4th in morbidity and mortality among Malaysian women. Currently, Magnetic Resonance Imaging (MRI) is considered as the gold standard imaging modality for tumours with a stage higher than IB2, due to its superiority in diagnostic assessment of tumour infiltration with excellent soft-tissue contrast. In this research, the robustness of semi-automatic segmentation has been evaluated using a flood-fill algorithm for quantitative feature extraction, using 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Radiomics features are not stable between the region of interest sizes and volumes on computed tomography and MRI, which was reported in a study using a homogenous phantom without any texture differences [19,20]. Ensuring the stability of radiomics features is crucial for the accuracy of image-based prognostication and external generalization of prognostic models [21][22][23][24][25][26][27][28][29][30][31]. In this study, ICCs were used to evaluate the repeatability and reproducibility of the radiomics features.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics features are not stable between the region of interest sizes and volumes on computed tomography and MRI, which was reported in a study using a homogenous phantom without any texture differences [19,20]. Ensuring the stability of radiomics features is crucial for the accuracy of image-based prognostication and external generalization of prognostic models [21][22][23][24][25][26][27][28][29][30][31]. In this study, ICCs were used to evaluate the repeatability and reproducibility of the radiomics features.…”
Section: Discussionmentioning
confidence: 99%
“…The quantization of the tumor lesion was deemed accurate in comparison to manual segmentation based on the uniform color present within the area of interest. Radzi et al (2021) previously showed that in order to accurately quantify the ROI, the optimal segmentation method requires images with good contrast enhancement [ 17 , 28 ]. In comparison to manual segmentation, it has been observed that a significant proportion of the tumor first-order features demonstrate a higher degree of reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The flood-filling algorithm determines connection in an area in a multi-dimensional array with the help of the similarity of intensity voxels to the selected node determined by users. In this method, nodes are added around the tumor region using a mouse cursor and when the flood-fill tool is activated, the ROI is segmented based on similar voxel intensity (Haniff et al 2021, Ramli et al 2022.…”
Section: Flood Filling (Ff)mentioning
confidence: 99%